Site Quality for Araucaria angustifolia Plantations with Subtropical Cambisol Is Driven by Soil Organism Assemblage and the Litter and Soil Compartments - Souza, Tancredo; Dobner, Mário; Batista, Diego Silva; Araujo, Damiana Justino; Nascimento, Gislaine dos Santos; da Silva, Lucas Jónatan Rodrigues [UNESP] (MDPI, 2024)
Different site quality levels in Araucaria angustifolia (Bert.) O. Kuntze plantations may influence the soil organisms and the interaction between litter and soil chemical properties by providing habitats and nutrients in different pathways. Our aim here was to understand the effect of site quality level in the interaction among litter, soil–solid phase, and organism assemblage on A. angustifolia, Campo Belo de Sul, Santa Catarina, Southern Brazil. In the low site quality, the litter deposition, litter K content, litter Ca content, soil organic matter, soil P content, soil K content, and soil exchangeable Ca reduced by 50.50, 49.54, 11.89, 20.51, 11.74, 61.18, and 35.18%, respectively, when compared to the high site quality. Nonmetric multidimensional scaling (NMDS) grouped the influence of site quality degree into three groups, considering the dissimilarities among soil organisms. The ordination of the soil organisms, richness, and Shannon’s diversity in each studied site quality degree had a stress value of 0.08. The structural equation models showed that the loss of site quality had a negative relationship with soil organism assemblage and soil and litter compartments. Our study highlights the fact that a fertile soil, a soil enriched in organisms, and enough litter support the forest productivity.
Keywords: k-factor; soil ecology in subtropical ecosystem; subtropical Cambisol properties